Cognitive remediation and brain connectivity: A resting-state fMRI study in patients with schizophrenia. (30th September 2020) - Penadés, Rafael; Segura, Bàrbara; Inguanzo, Anna; García-Rizo, Clemente; Catalán, Rosa; Masana, Guillem; Bernardo, Miquel; Junqué, Carme
Highlights: Patients with schizophrenia showed reduced connectivity in different brain networks. Psychological treatments induce detectable changes in connectivity networks. No significant treatment-specificity for the cognitive remediation were found. Abstract: Cognitive remediation is able to improve activation patterns in the frontal lobe but only few data on neuroconnectivity has been reported yet. Resting-state approach is a neuroimaging methodology with potentiality for testing neuroconnectivity in the context of cognitive remediation in schizophrenia. A resting-state fMRI data was acquired in part of the sample ( n = 26 patients, n = 10 healthy controls) of a partner study (NCT 02341131) testing the effects of cognitive remediation. A data-driven approach using independent component analysis (ICA) was used to identify functional brain networks, which were compared between groups and group per time using a dual-regression approach. ICA results revealed reduced functional connectivity between patients and controls in sensorimotor, basal ganglia, default mode and visual networks at baseline ( p <0.05 FWE-corrected). After treatment, time per group analyses evidenced increased connectivity in sensorimotor network. Furthermore, group comparison at follow-up showed similar connectivity patterns between patients and healthy controls in sensorimotor network, but also in default mode and basal ganglia networks. No differences between treatment groups were found. Our results add some evidence to the hypothesis of altered connectivity in schizophrenia, and the possibility to modify some aspects of brain connectivity networks after psychological interventions.